2020
DOI: 10.3389/fbioe.2020.00773
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cancer Cell Migration and Proliferation on Synthetic Extracellular Matrix Peptide Hydrogels

Abstract: Chemical and mechanical properties of a tumor microenvironment are essential players in cancer progression, and it is important to precisely control the extracellular conditions while designing cancer in vitro models. The study investigates synthetic hydrogel matrices from multi-arm polyethylene glycol (PEG) functionalized with collagen-like peptide (CLP) CG(PKG) 4 (POG) 4 (DOG) 4 alone and conjugated with either cell adhesion peptide RGD (mimicking fibronectin) or IKVAV (mimicking laminin). Human glioblastoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…Cell migration is altered by the biphasic hydrogel phenomenon associated with ligand density and cell adhesion, causing a traction force to be exerted on the substrate to move the cell [17,32]. It has been reported that focal adhesion affects cell migration due to mechanical stimuli obtained from the environment [33][34][35]. In this case, integrins as receptors will target the ECM by transmitting both outside-in signals and inside-out signals [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell migration is altered by the biphasic hydrogel phenomenon associated with ligand density and cell adhesion, causing a traction force to be exerted on the substrate to move the cell [17,32]. It has been reported that focal adhesion affects cell migration due to mechanical stimuli obtained from the environment [33][34][35]. In this case, integrins as receptors will target the ECM by transmitting both outside-in signals and inside-out signals [33].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that focal adhesion affects cell migration due to mechanical stimuli obtained from the environment [33][34][35]. In this case, integrins as receptors will target the ECM by transmitting both outside-in signals and inside-out signals [33]. Other studies have shown that the use of RGD peptides has the potential to inhibit cell migration [36].…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, bioactive motifs, such as RGD and isoleucine‐lysine‐valine‐alanine‐valine (IKVAV), could be conjugated to CMPs. [ 111 ]…”
Section: Structural Design As Ecm‐like Scaffoldsmentioning
confidence: 99%
“…Actually, peptide-based hydrogels have already shown their potential as a matrix for cell culture experiments creating adequate 3D microenvironments [ 137 , 138 , 139 , 140 ]. It has been demonstrated that they promote cell differentiation, stem cell proliferation, support the attachment of different kinds of cells, can be used for angiogenesis assays, and tumor cell migration and invasion tests [ 141 , 142 , 143 , 144 , 145 , 146 ]. Some hydrogel formulations are already in the market (e.g., Puramatrix, Hydromatrix, TrueGel3D).…”
Section: Biological Evaluation and Applications In The Biomedical Fieldmentioning
confidence: 99%